Comparative Study on the Antimicrobial Efficacy of Methanolic Extract of Root, Callus and Fruit Extracts of Myxopyrum smilacifolium Blume - Praveen, RP; Nair, Ashalantha (International Journal of Applied Sciences and Biotechnology, 2014)
The aim of the present study was to compare the antimicrobial efficacy of methanolic extract of root, callus and fruit of Myxopyrum smilacifolium Blume. Antimicrobial activity was tested using agar well diffusion with four bacterial strains viz: Escherechia coli, Enterococcus faecalis, Bacillus subtilis and Staphylococcus aureus of which E. coli alone was gram negative. The fungal strain employed was Candida albicans. Root extracts shown to be effective only against B. subtilis. Fruit extracts showed the maximum antimicrobial activity against all the microbial species considered for the current study except against S. aureus. Highlight of the present study was the antimicrobial activity of callus extracts. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11362 Int J Appl Sci Biotechnol, Vol. 2(4): 521-524